Role of the unfolded protein response in tumor cell characteristics and cancer outcome. Issue 1 (January 2017) - Galmiche, Antoine; Sauzay, Chloé; Chevet, Eric; Pluquet, Olivier
Abstract : Purpose of review: In the present review, we discuss the possible role of the unfolded protein response (UPR) in the acquisition of tumor cell characteristics and in the prognosis of cancer outcome, which could assist and contribute to the development of more promising therapeutic strategies. Recent findings: Accumulating evidence supports the idea that alteration of endoplasmic reticulum proteostasis is a key player in cancer development and aggressiveness. Some UPR components were reported as independent prognostic biomarker. Recent evidence supports a relationship between the UPR activation status and prognosis of tumors. This may represent an interesting avenue for better characterization of carcinogenesis and tumor type. Summary: The contribution of the UPR to the characteristics of malignant tumors is complex and dependent on both intrinsic (e.g. oncogene addiction) and extrinsic (e.g. hypoxia) contexts. Through adaptation to severe microenvironmental conditions, UPR branches are generally a survival strategy for cancer cells, which are able to cope with this challenging context. We address the question of whether the activation status of the UPR is related to tumor properties and discuss the role of the UPR in the clinical context.